An Analysis of Interpersonal Meaning in Coldplay’s Song ‘Fix You’ through Systemic Functional Linguistics - Amalia, Luqyana; Ramadhani, Tatsbita; Dewi, Intan Mustika; Rosiana, Rosiana (Dinamika Bahasa dan Budaya, 2026)
Music lyrics frequently convey social meaning and emotional depth. The emotional sentiments in Coldplay's song "Fix You" are powerful and offer hope, empathy, and encouragement. This study uses Halliday's Systemic Functional Linguistics (SFL) framework to investigate the interpersonal meaning in the lyrics of "Fix You," paying special attention to the mood and residue structures. The study interprets how linguistic choices convey relationships between the songwriter and listeners using a qualitative descriptive method in conjunction with content analysis. The results reveal that the majority of the phrases in "Fix You" employ declarative moods, suggesting that the singer wants to reassure and enlighten rather than tell or challenge. This is in keeping with the song's prevailing tone of empathy and support. To sum up, the interpersonal significance in “Fix You” represents emotional connection and reassurance, showing how linguistic choices contribute to the song’s comforting and motivational message. Keywords: Coldplay, Fix You, Interpersonal Meaning, Systemic Functional Linguistics, Mood and Residue.